Cenários: uma tecnologia para suportar a complexidade das redes de projeto - Hindrichson, Patricia Hartmann (Universidade do Vale do Rio dos Sinos, 2013)
The evolving information age has brought essential changes in production, distribution and consumption systems. Such transformation has conducted to changes in design processes, currently developed by complex design networks: they are open, interdisciplinary, cross-functional and interorganizational. In said context, scenario building techniques might be particularly useful for approaching the many actors involved towards certain issues as it aids the sharing of information and the elaboration of collaborative design knowledge. Even though the discipline diffusely employs this method, studies lack to refer to scenario building within the limits set out to design processes. Therefore, the main objective of this research is to discuss scenario building processes from the perspective of social, technological and disciplinary transformations. For that reason, an action-research strategy was chosen to allow active observation of the actors’ performance while building scenarios. Research and project were developed along the Sow Network Project, which is a collaborative enterprise focusing on the technological development of a web platform that allows information sharing among residents of a local community. The project is coordinated by a regional Technology Innovation Cluster (Pólo de Inovação Tecnológica do Vale do Paranhana – Encosta da Serra) and a local college (Faculdades Integradas de Taquara), and is funded by Rio Grande do Sul’s Department of Sciences, Innovation and Technologic Development. The reflections accomplished in this research contemplate issues associated with meaning and scenario building processes towards achieving a technology that enables mediating the complexity of collaborative design networks. As for the results, we have observed that scenarios could be understood as events that include interaction among the actors in codesign processes. Furthermore, it was evidenced that scenario practices are able to define a specific design strategy. The idea of “designing through scenarios” was discussed, as it is a technology that might catalyze the strategic feature of design by using building methods mainly focused on flexibility.
Keywords: Design estratégico; Cenários; Co-design; Redes de projeto; Strategic design; Scenarios; Design networks; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial